The virulence and reproduction of six entomopathogenic nematode strains of species Steinernema longicaudum to mealworm Tenebrio molitor in the laboratory conditions - Ngoc Chau, Nguyen; Tuan Anh, Do (Vietnam Journal of Biotechnology, 2022)
The virulence of and reproduction capacity of six entomopathogenic nematode strains of species Steinernema longicaudum (Rhabditida: Steinernematidae) to second stage larvae of mealworm Tenebrio molitor (Coleoptera: Tenebrionidae) was evaluated under laboratory conditions. An initial assessment with ten concentrations showed that mortality increased with the number of infective juveniles (IJs), and that the strain S-DM caused the highest mortality (97.2%) of T. molitor larvae. However, the effect of nematode strains and concentrations on the mortality of larvae was not statistically significant. The virulent of all nematode strains were moderately high with low lethal LC50 values between 43.8 and 47.6 IJs. The reproduction capacity of six nematode strains produced high yields between 65.700 and 79.700 IJs. The relationship between mealworm stage and concentrations of IJs was not significantly difference in all EPN strains. In all bioassays, the second stage of mealworms was the most susceptible. All these indigenous strains of species S. longicaudum might be adapted as potential agents in both categories, e.g. pathogenicity and reproduction capacity.